Enhancing Agricultural Land Processing Through Tillage Machine Utilization in Pangean Farmer Groups - Jhonni Rahman; Yulianto, Dody; Rizal, Yose; Subekti, Purwo; Asrol, Asrol; Anwar, Moh. Syaiful; Zuliantoni, Zuliantoni (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2025)
The use of plowing machines is an important innovation in horticultural farming systems because it can increase land efficiency and productivity. This activity aims to analyze the effectiveness of plowing machines in accelerating the soil cultivation process and its impact on increasing the productivity of horticultural farmers in the Jaya Makmur Farmers Group. A descriptive approach was used by observing the plowing machine's working process and comparing it with traditional soil cultivation methods commonly used by farmers. Data were obtained through field observations and interviews with farmer group members. The results showed that the use of plowing machines increased the speed of soil cultivation up to ten times faster than traditional methods. In addition, plowing machines resulted in more even soil inversion, creating more optimal soil conditions for horticultural plant growth. These findings confirm that the use of plowing machines not only saves time and labor but also has the potential to increase crop productivity through more efficient soil management. Thus, the use of plowing machines is a strategic solution to support increased efficiency and yields in horticultural cultivation.